Wojna chorwacko-serbska, nacjonalizm, seks i przekleństwa, czyli jak tłumaczono Vedranę Rudan - Skrzeszewska, Monika (Przekłady Literatur Słowiańskich, 2016)
War, Croatian nationalism, sex and swearwords — how has Vedrana Rudan’s books been translated? This article shows the various translations of Vedrana Rudan who is one of the most popular Croatian writers in Poland. A common view of translation says that focusing on a translation not the original is needed. That is why Polish culture, language and the reception of Croatian literature in Poland are key factors. Therefore in this article the problems with translating the Croatian language such as swearwords, sex and literary allusions into Polish have been shown. Key words: taboo, vulgarisms, translatability, untranslatability, Vedrana Rudan